Examining the Economic Behaviour Among Fisherman Community - Mintarti, Sri Umi; Wibowo, Agus (International Journal of Psychosocial Rehabilitation, 2020)
This study is aimed at examining the economics behaviour among fisherman community in Prigi, Watulimo District, Trenggalek Regency, Indonesiatechn. This study used descriptive qualitative to develop theories that are built through data obtained in the field. The results showed that the condition of the Prigi fishermen was still deficient in economic education and financial management. Therefore, it is necessary to increase economic knowledge and financial management. In order to obtain adequate thinking rationality to carry on life and fulfill daily needs. On the other hand, there is a need for training and provision of business assistance to increase the fishermen’s income from the catch. Uncertain catches and price monopoly snares by collectors make it difficult for fishers to expand their businesses outside the region. The urgent step that must be taken by the government is entrepreneurship training to realize how important it is to invest and make efforts to support the profession of fishers. Through this training, it is hoped that the fishing community, when meeting their immediate needs, does not always owe money. The results of our study offer the rationality and irrationality of the economic behavior of fishing communities that can be a strategic input for the government and stakeholders, in order to empower further and create prosperity for the fishing community.